Effects of Perilla frutescens var. acuta in amyloid β toxicity and Alzheimer's disease-like pathology in 5XFAD mice. (March 2022) - Cho, Eunbi; Lee, Jihye; Sin, Jae Seong; Kim, Sung-kyu; Kim, Chul Jin; Park, Mi Hee; Cho, Wan-Seob; Moon, Minho; Kim, Dong Hyun; Jung, Ji Wook
Abstract: Although accumulation of amyloid β (Aβ) plaque is a major hallmark of Alzheimer's disease (AD), various pathologies have been suggested therapeutic targets. Therefore, therapies-targeting multiple pathologies would be required for effective managements of AD. Accordingly, natural products, which has multiple active ingredients, have been receiving a lot of attention. In this study, we tested whether standardized ethanol extract of leaves of Perilla frutescens var. acuta (L.) Britt. (Lamiaceae) (ELPF) could modulate various pathologies in AD using 5XFAD mice. ELPF blocked Aβ aggregation and disassembled pre-formed Aβ aggregates. ELPF blocked Aβ aggregates-induced LTP impairment and ELPF-disassembled Aβ aggregates failed to impair hippocampal LTP. Systemic administration of ELPF blocked Aβ aggregates-induced memory impairment in a passive avoidance test. ELPF-disassembled Aβ aggregates failed to impair passive avoidance memory. Prolonged administration of ELPF ameliorated memory impairments in 5XFAD mice. In the hippocampus of 5XFAD mice, ELPF administration significantly reduced Aβ deposits and neuroinflammation. These results demonstrate that ELPF could be a promising therapeutic candidate for AD.